2015
DOI: 10.1186/s13229-015-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced isolation-induced pup ultrasonic communication in mouse pups lacking brain serotonin

Abstract: BackgroundSerotonin (5-hydroxytryptamine, 5-HT) is a key modulatory neurotransmitter in the mammalian central nervous system (CNS) that plays an important role as a developmental signal. Several lines of evidence associate altered 5-HT signaling with psychopathology in humans, particularly neurodevelopmental disorders such as autism spectrum disorders (ASD). ASD are characterized by persistent social and communication deficits along with stereotyped and repetitive patterns of behavior, with all symptoms emergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 88 publications
(121 reference statements)
5
36
0
Order By: Relevance
“…6a). Similar phenotypes of altered pup USVs are reported in D2 dopamine receptor null mice 36 , tryptophan hydroxylase 2 null mice 37 , and shank3 null mice 38 . Both decreased pup USVs and territory marking are noted in shank1 null mice 39 .…”
Section: Giant Ankb Mutant Mice Exhibit Penetrant Innate Social Deficitssupporting
confidence: 73%
“…6a). Similar phenotypes of altered pup USVs are reported in D2 dopamine receptor null mice 36 , tryptophan hydroxylase 2 null mice 37 , and shank3 null mice 38 . Both decreased pup USVs and territory marking are noted in shank1 null mice 39 .…”
Section: Giant Ankb Mutant Mice Exhibit Penetrant Innate Social Deficitssupporting
confidence: 73%
“…Whether the different call types in rat pups, such as the present ones, may be differentially effective in this respect, is not known. However, it has been shown that certain spectral features of pup calls, like call length, peak frequency, or amplitude may play a role in mice (Smith, , Ehret, , Liu & Miller, , Wöhr et al, , for review, see Wöhr & D'Amato, ) and that the clustering of call types is affected in mouse pups lacking genes implicated in social behavior and communication (Mosienko et al, ; Sungur et al, ; Wöhr, ). In rats, it was shown that playback of natural isolation‐induced USV leads to maternal search behavior, while no such response was seen in mothers exposed to 40‐kHz sine wave tones (Wöhr & Schwarting, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we aimed to classify these calls into different types, based on observational methods and by means of spectrographic features, since previous studies have shown that pup USV may be assigned to different types, which, dependent on the method, may range between 2 and 13 types (e.g., Brudzynski et al, , Hashimoto, Moritani, Aoki‐Komori, Tanaka, & Saito, ; Zeskind et al, ). While such previous classifications are based on visual inspection of spectrograms, primarily focusing on call shapes, we aimed for a different, and probably less subjective, classification by means of a quantitative approach including acoustic features, such as frequency modulation, peak frequency, and call duration, previously applied in mouse pups (Mosienko, Beis, Alenina, & Wöhr, ; Sungur, Schwarting, & Wöhr, ; Wöhr, ; Wöhr et al, ). Defining call types is important, since certain ones may specifically be affected, for example, by pre‐ or neonatal manipulations (Barren & Gilbertson ; Harmon et al, ; Krüger & Hanganu‐Opatz, ; Tonkiss et al, ), and it is reasonable to assume that different genetic backgrounds, like in the three outbred stocks, may also affect them.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mice lacking tryptophan hydroxylase 2, responsible for central 5-HT synthesis, show decreased ultrasonic vocalizations, decreased sniffing of social odors, apparent deficits in social memory, and cognitive inflexibility (Kane et al, 2012, Del’Guidice et al, 2014, Mosienko et al, 2015). Mice lacking MAOA, responsible for breaking down 5-HT, show decreased social approach, decreased ultrasonic vocalizations, and impaired reversal learning (Bortolato et al, 2013).…”
Section: Other Rodent Models Of Altered 5-ht Function Relevant To Asdmentioning
confidence: 99%